Organizational Communication Strategy in Achieving Performance Targets in the Deputy for Resources and Institutions - Gunawan Prasetyo; Gloria Angelita; Marlinda Irwanti (MIMBAR : Jurnal Sosial dan Pembangunan, 2026)
An effective organizational communication strategy is crucial for improving employee productivity, as it facilitates clear messaging and fosters mutual understanding between leaders and employees. This study highlights the importance of communication planning to avoid misunderstandings and ensure optimal information dissemination. Using a qualitative approach with a constructivist paradigm through observation, in-depth interviews, documentation studies, and data triangulation, this study demonstrates that open, participatory organizational communication supported by the use of digital media can build shared understanding, increase policy acceptance, strengthen cross-unit coordination, and encourage collective action in achieving performance targets. These findings demonstrate that organizational communication is a strategic instrument linking institutional transformation, policy adaptation, and performance achievement. effective way to increase employee productivity and ensure timely delivery of information, especially during critical periods such as policy changes and budget changes.